Abnormal amplitude of low-frequency fluctuations associated with sleep efficiency in major depressive disorder - Li, Yifei; Zhao, Wenming; Li, Xinyu; Guan, Lianzi; Zhang, Yu; Yu, Jiakuai; Zhu, Jiajia; Zhu, Dao-min (Journal of psychiatric research, 2024)
Sleep disturbance is one of the most frequent somatic symptoms in major depressive disorder (MDD), but the neural mechanisms behind it are not well understood. Sleep efficiency (SE) is a good indicator of early awakening and difficulty falling asleep in MDD patients. Our study aimed to investigate the relationship between sleep efficiency and brain function in MDD patients. We recruited 131 MDD patients from the Fourth People's Hospital in Hefei, and 71 well-matched healthy controls who were enrolled from the community. All subjects underwent resting-state functional MRI. Brain function was measured using the fractional amplitude of low-frequency fluctuation (fALFF), sleep efficiency was objectively measured by polysomnography (PSG), and clinical scales were used to evaluate depressive symptoms and sleep status. Multivariate regression analysis was performed to assess the relationship between the amplitude of the low frequency fluctuation fraction and sleep efficiency. Three brain regions with relevance to sleep efficiency in MDD patients were found: inferior occipital gyrus (Number of voxels = 25, peak MNI coordinate x/y/z = −42/-81/-6, Peak intensity = 4.3148), middle occipital gyrus (Number of voxels = 55, peak MNI coordinate x/y/z = −30/-78/18, Peak intensity = 5.111), and postcentral gyrus (Number of voxels = 26, peak MNI coordinate x/y/z = −27/-33/60, Peak intensity = 4.1263). But there was no significant relationship between fALFF and SE in the healthy controls. The reduced sleep efficiency in MDD may be related to their lower neural activity in the inferior occipital gyrus, middle occipital gyrus, and postcentral gyrus. The findings may provide a potential neuroimaging basis for the clinical intervention in patients with major depressive disorder with sleep disturbances.